Biaxial fatigue behavior of a powder metallurgical TRIP steel (Fracture and Structural Integrity, 2015)
Multiaxial fatigue behavior is an important topic in critical structural components. In the present study the biaxial-planar fatigue behavior of a powder metallurgical TRIP steel (Transformation Induced Plasticity) was studied by taking into account martensitic phase transformation and crack growth behavior. Biaxial cyclic deformation tests were carried out on a servo hydraulic biaxial tension-compression test rig using cruciform specimens. Different states of strain were studied by varying the strain ratio between the axial strain amplitudes in the range of -1 (shear loading) to 1 (equibiaxial loading). The investigated loading conditions were proportional due to fixed directions of principal strains. The studied TRIP steel exhibits martensitic phase transformation from ?-austenite via ?-martensite into ?‘- martensite which causes pronounced cyclic hardening. The ?‘-martensite formation increased with increasing plastic strain amplitude. Shear loading promoted martensite formation and caused the highest ?‘-martensite volume fractions at fatigue failure in comparison to uniaxial and other biaxial states of strain. Moreover, the fatigue lives of shear tests were higher than those of uniaxial and other biaxial tests. The von Mises equivalent strain hypothesis was found to be appropriate for uniaxial and biaxial fatigue, but too conservative for shear fatigue, according to literature for torsional fatigue. The COD strain amplitude which is based on crack opening displacement gave a better correlation of the investigated fatigue lives, especially those for shear loading. Different types of major cracks were observed on the sample surfaces after biaxial cyclic deformation by using electron monitoring in an electron beam universal system and scanning electron microscopy (SEM). Specimens with strain ratios of 1, 0.5, -0.1 and -0.5 showed mode I major cracks (perpendicular to the axis of maximum principal strain). Major cracks after shear fatigue had partially mode II orientation (tilted 45° to the loading axes) and afterwards bifurcated into two pairs of mode I cracks. Another shear test revealed a major crack of mode I orientation (parallel to the loading axes). These results are in good agreement to the literature. Micro cracks after shear fatigue were longer than those after biaxial fatigue with strain ratios of 1 and 0.5. Major and minor cracks after equibiaxial and shear loading showed crack branching and crack coalescence. The results on fatigue crack behavior support the assumption that the period of stage I (mode II) crack propagation is much longer under shear loading than under other biaxial conditions due to absence of tensile stress normal to the planes of maximum shear strain under shear loading.
Keywords: Biaxial fatigue